Texture Control of Pure Titanium Sheet by the Surface Effect during Phase Transformation - Kai Li; Ping Yang; Feng-e Cui; Weimin Mao (Metals, 2018)
The texture evolution of cold rolled pure titanium through different annealing parameters was investigated and different processes for various textures controls were proposed for further industrial application. Columnar grains with strong {11–20}//RD (rolling direction) texture was produced through cold rolling and a cooling-controlled annealing at 1100 °C with the Ar atmosphere. The preferred nucleation on the surface and the lowest strain energy of variant pairs during grain growth caused the formation of columnar grains and variant selection. Texture inheritance was discovered both in the cold-rolled and warm rolled-pure titanium sheets following 1000 °C annealing. The stored energy during cold rolling was the main reason causing the texture inheritance. Basal texture could be produced through warm rolling and subsequent annealing. The 30°-rotated around RD from basal texture could be preserved through both recrystallized annealing and transformed annealing.